PENGARUH PERSEPSI KEMUDAHAN, MANFAAT, KEAMANAN DAN RISIKO TERHADAP MINAT MENGGUNAKAN LAYANAN MOBILE BANKING - Shinta Shillviana Rahmawati; Suhendro; Riana Rachmawati Dewi (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
ABSTRACT This study aims to determine the factors that can influence interest in using mobile banking services, namely perception of convenience, perception of benefits, perception of security and perception of risk. This type of research uses quantitative research. The population used is Bank Syariah Indonesia customers with a sample size of 100 respondents. The sample requirements used in this study are Bank Syariah Indonesia customers domiciled in Boyolali Regency who have used mobile banking services. This study uses probability sampling techniques with purposive sampling methods. The data used in this study are primary data in the form of questionnaires that will be processed using SPSS software version 21.0. The results of the analysis used in this study are multiple linear regression analysis. The results of the research that has been conducted indicate that perception of convenience, perception of security, and perception of risk have a positive and significant effect on interest in using mobile banking services. While the perception of benefits does not affect interest in using mobile banking services. Keywords: Interest in Using; Mobile Bankin; Perceived Convenience; Perceived Benefits; Perceived Security; Perceived Risk